2023
DOI: 10.4103/jehp.jehp_922_22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin receptor blocker as antihypertensive in assessing mortality in patients of COVID-19: A single tertiary care center study

Abstract: BACKGROUND: The angiotensin-converting enzyme 2 (ACE2) receptor, a membrane receptor present in the respiratory system, the gastrointestinal tracts, the heart, and the kidney is the entry point for SARS-CoV-2 to enter human cells. Concerns were raised about the influence of using antihypertensive drugs like angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) in individuals with COVID-19 due to its tight relationship with the ACE2 receptor. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This result is not surprising since all hypertensive patients in the present cohort were receiving therapy with angiotensin-converting enzyme inhibitors. A recent study on the use of ACE inhibitors for hypertensive patients with COVID-19 infection showed the protective effects of these drugs on the severity of the disease in terms of mortality, highlighting that in this group of patients, there was less disease severity and a reduced risk of admission to intensive care [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not surprising since all hypertensive patients in the present cohort were receiving therapy with angiotensin-converting enzyme inhibitors. A recent study on the use of ACE inhibitors for hypertensive patients with COVID-19 infection showed the protective effects of these drugs on the severity of the disease in terms of mortality, highlighting that in this group of patients, there was less disease severity and a reduced risk of admission to intensive care [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nor did we assess some potential confounding factors, such as previous SARS-CoV-2 infection or time between the data of vaccination and the onset of disease. Moreover, it would have been interesting to consider the effects of the restrictive measures, the risk management, and the communication plans implemented by the government during the pandemic [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…4, Because we excluded patients with a history of heart failure, the findings of this study cannot be applied to these patients. 5, Due to the nature of our cross-sectional study on admission data, information regarding the utilization of angiotensin receptor blockers, 29 which may affect NT-proBNP and mortality, is currently unavailable. However, we intend to delve deeper into this aspect through future investigations.…”
Section: Discussionmentioning
confidence: 99%